Базовий сценарій довгострокового розвитку національної промисловості до 2035 року - Okhten, Oleksiy O.; Dasiv, Alla F. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The article formulates the assumptions for the baseline scenario for the development of Ukrainian industry as to the dynamics of the world economy, world food and commodity price indices, the population size of Ukraine, the exchange rate of hryvnia against the dollar and the euro, the dynamics of wages in Ukraine and the EU, the propensity to invest in the Ukrainian economy, the value of the world GDP deflator. The initial data for the base scenario for the development of Ukrainian industry in 2020-2035 have been determined. The baseline scenario is conservative and reflects the continuing trends in the national industry that were observed until 2019.The main results of modeling the baseline scenario for the development of the national industry for 2020-2035 by sectors have been presented. The growth rates of value added by sectors, as well as the growth rates of GDP from 2010 to 2035 have been calculated. Changes in the share of sectors of the economy of Ukraine for 2011-2020 (fact) and from 2021 to 2035 (basic scenario) have been presented.It should be noted that the development of the scenarios was based on the continuation of the trends of 2010-2019 without taking into account unpredictable factors (such as the coronavirus pandemic or military combat), so the main goal is to assess general economic trends and factors rather than accurately predict certain indicators in specific conditions.The dynamics of relative indicators that indicate the structural features of the process of value added creation was calculated and analyzed, including capital-labor ratio, capital productivity, efficiency of labor costs and labor productivity for each sector.It has been established that in the baseline scenario, the economy of Ukraine will experience steady growth in the main sectors: mining, by an average of 1% per year; agriculture by 2-2.5% per year, while the largest growth will be observed in the processing industry, above 4% per year. This is generally in line with the trends in the global economy: growth is mainly concentrated in processing industries rather than industries that extract natural resources. The annual GDP growth, according to the simulation results, will be in the range of 3-5%, which approximately corresponds to the forecasts of various world institutions.